Enabling critical pedagogy in higher education - Seal, Mike; Smith, Alan (Critical practice in higher education., 2021)
An essential introduction to critical pedagogy for all those working within higher education, re-examining the concept and exploring its practical application at an institutional level, within the curriculum, within assessment, through learning and teaching, and in the spaces in-between.